Evolution of body size and trophic position in migratory fishes: a phylogenetic comparative analysis of Clupeiformes (anchovies, herring, shad and allies). (22nd August 2018) - Bloom, Devin D; Burns, Michael D; Schriever, Tiffany A
Abstract: Migration is a widespread phenomenon among animals and has a profound influence on the evolution of species traits. Diadromous fishes provide an extreme example of migration, moving between marine and freshwaters, often travelling thousands of kilometres for feeding and reproduction. Diadromy has been linked to changes in feeding ecology, body size and various life-history attributes. However, most studies have focused on intraspecific variation and associated mechanisms. In this study, we use phylogenetic comparative methods to analyse body size and trophic position across Clupeiformes (anchovies, herring, shad and allies), a large clade of fishes that includes both diadromous and non-diadromous species. We found that diadromous species are larger than non-diadromous species, but there is no difference in trophic position, and that these patterns are not attributable to common ancestry. Diadromous species show a decoupling of body size and trophic position, whereas non-diadromous clupeiforms have a positive relationship between body size and trophic position. Using a model-fitting approach, we detected a signal of strong selection driving diadromous fishes to different adaptive peaks from non-diadromous fishes for body size, but a single adaptive peak for trophic position. We suggest that diadromous fishes have evolved larger body size than obligate marine and freshwater species as an adaptation to maximize energy expenditure during long-distance migration.